Ikhtiar Cegah Stunting Melalui Kontekstualisasi Fikih Parenting - Husain, Husain; Sufyan Mubarak; Intan, Nur (Sekolah Tinggi Agama Islam Negeri Majene, 2023)
In fact, parenting jurisprudence does not only target children physically until they are mumayyiz (able to choose and choose good actions) as is found in many classical jurisprudence books, but also their psychology, including their mental and economic readiness for marriage. Until now, the main trigger for many cases of stunting is still caused by early marriage. Early marriage occurs because child care is only oriented towards meeting the child's physical needs, while spiritual needs still do not receive significant attention. Efforts in this direction can be made by contextualizing parenting jurisprudence that parenting is not only about the child's physical aspects but also spiritual aspects and economic readiness. This is reflected in the history of the Prophet's life as a child, receiving maximum nurturing education both regarding his physical and psychological well-being, as well as economic readiness, with the Prophet being included in every trade mission with his uncle. The implications of this contextualization of parenting jurisprudence are at least a new orientation of parenting jurisprudence in efforts to minimize stunting. Apart from that, it also serves as a legal standing for child care activities to comprehensively pay attention to children's physical, psychological and economic readiness.